Serological survey of Neospora caninum in dairy herds from Parauapebas, State of Pará - Clovis Laurindo Silva (Semina: Ciências Agrárias, 2015)
Neospora caninum is a coccidian protozoan that affects cattle worldwide causing economic losses. To survey the frequency of anti-N. caninum antibodies in dairy herds in the municipality of Parauapebas, Southeast of Pará, samples of 465 sera from 45 farms were subjected to indirect immunofluorescence assay (cutoff 1:100). Anti-N. caninum antibodies were found with a frequency of 13,33% with the following titer distribution: 27 (43,55%) for titer 100; 14 (22,58%) for 200; 16 (25,80%) for 400, and 5 (8,07%) for 800; no serum titers more than 800 was noted, but at least one positive animal was present in most farms. The highest frequency occurred among females, with no significant difference in frequency between the sexes (Fisher exact test = 0,59, P = 0,99); 2-year-old animals had the highest frequency, although their numbers were lesser than those aged >5 years, with no significant difference in frequency between the age groups (χ2 = 2,1, P = 0,71). No significant difference was observed between the frequency and occurrence of abortion (χ2 = 2,3, P = 0,13) and frequency and presence of dogs in the farms (χ2 = 0,26, P = 0,60). Actions toward health monitoring are recommended to prevent the entry of new sources of N. caninum and to control its spread within herds.